2019
DOI: 10.1038/s41598-019-51495-0
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Cr isotope signals track the variably anoxic Cryogenian interglacial period with voluminous manganese accumulation and decrease in biodiversity

Abstract: Earth’s atmosphere experienced a step of profound oxygenation during the Neoproterozoic era, accompanied by diversification of animals. However, during the Cryogenian period (720–635 million years ago) Earth experienced its most severe glaciations which likely impacted marine ecosystems and multicellular life in the oceans. In particular, large volumes of Mn and Fe accumulated during the interglacial intervals of the Cryogenian glaciations, indicating large anoxic marine metal reservoirs. Here we present chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…For example, many studies of the redox state of seawater during this period have focused on the Nanhua Rift Basin in the south-eastern Yangtze Platform, where Mn deposits in the Datangpo Formation exist [43][44][45][46][47][48][49][50]. A series of proxies used to reconstruct the redox environment of the Datangpo Formation indicate that the deep water column in the Nanhua Rift Basin might have experienced a redox transition from an anoxic state during the Sturtian glaciation to a temporarily oxygenated state during the Mn metallogenic era (Figure 3).…”
Section: Redox-stratified Water Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, many studies of the redox state of seawater during this period have focused on the Nanhua Rift Basin in the south-eastern Yangtze Platform, where Mn deposits in the Datangpo Formation exist [43][44][45][46][47][48][49][50]. A series of proxies used to reconstruct the redox environment of the Datangpo Formation indicate that the deep water column in the Nanhua Rift Basin might have experienced a redox transition from an anoxic state during the Sturtian glaciation to a temporarily oxygenated state during the Mn metallogenic era (Figure 3).…”
Section: Redox-stratified Water Systemmentioning
confidence: 99%
“…Coincidentally, if this redox transition happened to encounter substantial amounts of dissolved Mn(II) stored in the anoxic water column within the relatively enclosed basins, episodic ventilation with cold oxygenated surface water would then have induced large-scale Mn sedimentation. Elemental and isotopic proxies for reconstructing paleoenvironmental oxygenation during deposition of the Sturtian-age Tiesi'ao Formation and the 1 st (Mn ores and black shales overlying the Mn layers) and 2 nd members of the Datangpo Formation (data sources: N isotopes [44]; Fe species [46]; Fe isotopes [48]; Cr isotopes [49]; Cd isotopes (SW: surface water; DW: deep water) [50]). [44]; Fe species [46]; Fe isotopes [48]; Cr isotopes [49]; Cd isotopes (SW: surface water; DW: deep water) [50]).…”
Section: Redox-stratified Water Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr isotopes in ancient marine carbonates and shales are increasingly used to reconstruct the oxygenation history of the atmosphere‐hydrosphere system (Canfield et al., 2018; Cole et al., 2016; Frank et al., 2019; Frei et al., 2011; Gilleaudeau et al., 2016; Holmden et al., 2016; Planavsky et al., 2014; Wei, Frei, et al., 2018; Wei, Frei, et al., 2020; Xu et al., 2019) In a continental setting Cr is most commonly present as Cr(III) in igneous minerals and is characterized by a narrow isotopic range of δ 53 Cr = −0.124 ± 0.101‰ (Schoenberg et al., 2008), with the exception of some altered mafic and ultramafic rocks that are positively fractionated compared to the igneous baseline (Farkaš et al., 2013; Shen et al., 2015). The oxidation of Cr(III) to Cr(VI) is catalyzed by MnO 2 , which is only stable above a threshold value of atmospheric oxygen estimated to be between 0.03% and 1% of PAL based on kinetic constraints (Crowe et al., 2013; Planavsky et al., 2014).…”
Section: Background: Cr Isotopes and Ree + Ymentioning
confidence: 99%
“…The seawater under the ice sheet was in a reduced state, and Mn and Fe could accumulate as ionic compounds (Mn 2+ and Fe 2+ ) in large quantities, which provided a material basis for the subsequent precipitation and enrichment of manganese [13,43,44]. Previous studies have shown that the Nanhua Basin was in a redox stratified environment in the Datangpo stage [45][46][47], and the oxidation of the water in the basin gradually increased, forming the suboxidation-oxidation environment in the shallow parts [48][49][50]. In the process of progressive oxidation in the marine environment after glaciation, Fe 2+ was oxidized and precipitated before Mn 2+ , leading to the first-stage separation of Mn and Fe [51].…”
Section: Separation Of Mn and Fe During Sedimentationmentioning
confidence: 99%